Beretning om agrikulturkemisk Virksomhed. Ved generalforsamling d. 17. Decbr. 1895. - Stein, V. (Tidsskrift for Landøkonomi, 2018)
Beretning om agrikulturkemisk Virksomhed. Ved generalforsamling d. 17. Decbr. 1895.